Goblet cell carcinoid of the rectum: a case report - Yoshiyuki Inoue; Hisanaga Horie; Yuko Homma; Ai Sadatomo; Makiko Tahara; Koji Koinuma; Hironori Yamaguchi; Toshiki Mimura; Atsushi Kihara; Alan Kawarai Lefor; Naohiro Sata (Surgical Case Reports, 2020)
Abstract Background Goblet cell carcinoid (GCC) is a neuroendocrine tumor usually found in the appendix. GCCs exhibit characteristic findings with mixed endocrine-exocrine features such as staining positive for neuroendocrine markers and producing mucin. The primary GCC of the rectum is exceedingly rare. Case presentation A 77-year-old Japanese male presented with hematochezia. Anal tenderness and a hard mass in the anal canal were found on the digital rectal examination, and colonoscopy was performed. Colonoscopy showed an irregularly shaped mass in the anal canal. Biopsy showed mixed features including adenocarcinoma in situ, well-differentiated adenocarcinoma, and mucinous carcinoma with invasive proliferation. No metastatic lesions were found on the computed tomography scan. Pelvic magnetic resonance imaging scan showed extramural growth of a tumor on the ventral side of the rectum without invasion to the prostate. Laparoscopic abdominoperineal resection was performed. The final diagnosis was well-differentiated adenocarcinoma in the mucosa and goblet cell carcinoid from the submucosa to the adventitia of the rectum. The patient was discharged from the hospital on postoperative day 16. Six months after resection, a computed tomography scan revealed multiple metastatic lesions in the liver. Several chemotherapy regimens were given, and the patient has stable disease 27 months after surgery. Conclusion We present a patient with rectal GCC with metachronous liver metastases. Since GCC grows intramurally and is biologically aggressive compared to typical carcinoid lesions, the disease is usually diagnosed at an advanced stage. The development of optimal adjuvant chemotherapy is needed for those patients.